Microleakage of Direct Restorations-Comparisonbetween Bulk-Fill and Traditional Composite Resins:Systematic Review and Meta-Analysis - Zotti, Francesca; Falavigna, Edoardo; Capocasale, Giorgia; De Santis, Daniele; Albanese, Massimo (European Journal of Dentistry, 2021)
Since the bulk-fill composites were produced, there was a progressive diffusion of their use for direct conservative treatment in posterior teeth. Their chemical structure increases the depth of cure and decreases the polymerization contraction; in this manner, bulk-fill composites can be placed in 4 mm single layers and the treatment times are considerably reduced. However, aesthetic and mechanical properties and impact on microleakage of bulk-fill resins are still unclear.This systematic review and meta-analysis aimed to assess the risk of microleakage of direct posterior restorations made of bulk-fill versus conventional composite resins.Researches were performed on PubMed and Scopus databases. Eligible in vivo studies, published since 2006, were reviewed. Outcomes of marginal discoloration, marginal adaptation, and recurrent caries were considered to conduct the systematic review and meta-analysis. Secondary data were examined to implement additional analysis and assess the risk of bias.Eight randomized clinical trials were analyzed, involving 778 direct restorations. The summary of RCTs led to significant but inconsistent results; the marginal discoloration and recurrent caries were found to be improved respectively by 5.1 and 1.4%, whereas the marginal adaptation was reduced of 6.5%. Secondary analyses revealed that follow-up periods, the adhesive system used and the class of carious lesions evaluated are confounding factors, and they result in a risk of bias across studies.Bulk-fill composites are innovative materials for conservative dentistry and they can be used to reduce treatment steps and duration of operative times. There are insufficient data to explore the relationship between bulk-fill composites and microleakage and further investigations are needed.
Keywords: bulk-fill composites; microleakage; marginal discoloration; marginal adaptation; recurrent caries; direct restorations